Behavioral and molecular disruptions in honey bees induced by lithium chloride exposure - Mojtaba Esmaeily (Scientific Reports, 2025)
Abstract Lithium chloride (LiCl) has emerged as a promising alternative to synthetic acaricides for controlling Varroa destructor, a major threat to honey bee health. However, its potential side effects on bees and their products require further investigation. This study aimed to assess the effects of LiCl on honey bee health, focusing on survival, behavior, and molecular responses. We investigated the effects of varying doses and feeding durations of LiCl on honey bee survival, aggression, stress- and immune-related gene expression, and recovery potential after treatment cessation. Our results show that LiCl feeding reduced honey bee survival in a dose-dependent manner, with higher concentrations leading to greater accumulation of lithium in bee tissues. Furthermore, LiCl suppressed aggression behavior and altered the gene expression related to honey bee health, such as vitellogenin, antimicrobial peptides, antioxidant enzymes, and heat shock proteins. The duration of LiCl feeding was a critical factor, as shorter feeding periods followed by recovery with control diets restored gene expression and survival rates to the levels of control groups. These findings highlight the importance of optimizing LiCl dosage and feeding duration to balance its Varroa controlling efficacy with honey bee safety, and further research is needed to ensure its long-term safety for colonies and ecosystems.